Does hyperthyroidism predispose to thioridazine-induced hyperpyrexia and cardiac arrhythmias?. Issue 704 (June 1984) - Murphy, M. B.; FitzGerald, M. X.
Abstract : Treatment with thioridazine resulted in hyperpyrexia and ventricular tachycardia in a young woman who was later shown to have thyrotoxicosis. The reasons why hyperthyroidism may enhance thioridazine toxicity are reviewed.